Financial literacy and self-control in FinTech: Evidence from a field experiment on online consumer borrowing - Di Bu; Tobin Hanspal; Yin Liao; Yong Liu (Leibniz Institute for Financial Research SAFE, 2020)
We report the results of a longitudinal intervention with students across five universities in China designed to reduce online consumer debt. Our research design allocates individuals to either a financial literacy treatment, a self-control training program, or a zero-touch control group. Financial education interventions improve test scores on general financial literacy but only marginally affect future online borrowing. Our self-control treatment features detailed tracking of spending and borrowing activity with a third-party app and introspection about individuals' consumption with a counselor. These sessions reduce future online borrowing, delinquency charges, and borrowing for entertainment reasons - and are driven by the male subjects in the sample. Our results suggest that self-regulation can affect financial behavior in e-commerce platforms.
Keywords: G51; G53; D14; D18; G23; G21; 330; Financial literacy; online borrowing; Consumer credit; Self-control; FinTech; China